The late palaeolithic habitation of Haule V from excavation report to the reconstruction of Federmesser settlement patterns and land use (Van Gorcum, 1996)
The Haule V site is compared with other Federmesser settlements in the Northwest European plain and with archaeological, ethno-archaeological and ethnohistorical censuses of settlements, population, and land use of 70 analogous arctic and subarctic collector societies in North America.